Sodium-ion battery positive electrode material with high cycle performance and preparation method thereof
By doping magnesium, titanium, nickel, and aluminum elements into the positive electrode material of sodium ion battery and coating the conductive polymer, the problems of poor structural stability and insufficient rate performance during the circulation process are solved, and high cycle stability is achieved and good rate performance.
Patent Information
- Application Number
- CN202411590223.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-02-18
AI Technical Summary
The existing sodium ion battery positive electrode materials have poor structural stability and insufficient rate performance during the cycle process. Especially under high rate conditions, structural collapse and volume changes are prone to rapid attenuation of battery capacity.
The layered transition metal oxide NaxMnyO2 doped with magnesium, titanium, nickel and aluminum elements is used as the positive electrode material, and the surface is coated with conductive polymer to optimize the electrochemical performance and structural stability of the material.
It significantly improves the cycle stability and rate performance of the positive electrode material of sodium ion battery, extends the service life and cycle performance of the battery, especially in the high-rate charging and discharging conditions, which can maintain a good capacity retention rate.
Smart Images

Figure CN119480969A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of sodium ion battery positive electrode materials, and in particular relates to a sodium ion battery positive electrode material with high cycle performance and a preparation method thereof. Background Art
[0002] The cathode material of sodium ion battery is a key component of sodium ion battery, which determines the energy density, cycle life and safety performance of the battery. Similar to lithium ion battery, the working principle of the cathode material of sodium ion battery is to store and release electric energy by embedding and de-embedding sodium ions between the positive electrode and the negative electrode. Due to the abundant sodium resources, low cost and wide distribution, sodium ion battery is considered to be a potential solution to replace lithium ion batteries, especially suitable for large-scale energy storage systems. Common cathode materials of sodium ion battery include layered transition metal oxides, Prussian blue compounds, polyanion materials, etc. These materials have their own advantages and disadvantages. For example, layered transition metal oxides have high theoretical capacity and good rate performance, but they are prone to structural collapse during the cycle; Prussian blue compounds have good ion migration channels and high working voltage, but their synthesis process is relatively complicated; polyanion materials are concerned for their structural stability and good cycle performance, but their conductivity is relatively low.
[0003] Moreover, the diversity of sodium-ion battery cathode materials makes it have wide application potential in many fields. First, sodium-ion batteries are very suitable for large-scale energy storage systems, such as the storage of renewable energy and the maintenance of distributed power grid stability due to the abundance and low cost of raw materials. In these applications, sodium-ion batteries can provide efficient and long-lasting energy storage solutions, which help solve the problem of unstable renewable energy generation. Secondly, sodium-ion batteries are also suitable for small and medium-sized energy storage devices, such as home energy storage systems and uninterruptible power supply systems, which require batteries to have good cycle life and safety. In addition, sodium-ion batteries are also beginning to be used in electric vehicles and light electric vehicles, which usually require batteries to have high energy density and long service life. With the continuous development and optimization of sodium-ion battery technology, especially the innovation in cathode materials, its application prospects in consumer electronics, smart grids, renewable energy storage and other fields will be broader.
[0004] Existing positive electrode materials for sodium-ion batteries face many challenges in practical applications, mainly manifested in poor cycle stability and insufficient rate performance. Especially under high-rate conditions, traditional materials such as sodium nickel manganese oxide are prone to structural collapse and volume changes during the charge and discharge process. These structural changes will lead to an increase in lattice energy, causing stress and strain inside the material to be concentrated in specific areas, resulting in poor contact between particles and gradual pulverization of electrode materials, which seriously affects the conductivity of the electrode and the ion migration channel, and ultimately leads to rapid decay of the battery capacity; in addition, the interface between sodium-ion battery materials and electrolytes is unstable. During long-term cycles, the solvent molecules of the electrolyte and their decomposition products may react with the electrode surface to form an unstable side reaction layer. These side reactions not only consume active materials, but also hinder the transmission of ions and increase the internal resistance of the battery, resulting in a decrease in the coulombic efficiency of the battery and thermal management problems, further accelerating the aging of electrode materials and the degradation of battery performance, thereby significantly shortening the cycle life and service life of the battery.
[0005] In view of this, the present invention is proposed. Summary of the invention
[0006] The technical problem to be solved by the present invention is to overcome the deficiencies of the prior art, provide a sodium ion battery positive electrode material with high cycle performance and a preparation method thereof, and solve the problems raised in the above background technology.
[0007] In order to solve the above technical problems, the basic concept of the technical solution adopted by the present invention is:
[0008] A sodium ion battery positive electrode material with high cycle performance, the positive electrode material is a layered transition metal oxide Na x Mn y O2, doped with magnesium, titanium, nickel, and aluminum elements, with a doping ratio of 5-10% magnesium, 2-5% titanium, 8-12% nickel, and 3-7% aluminum, and surface coated with a conductive polymer, where 0.5≤x≤1.0, 0.5≤y≤1.0. Among them, magnesium can increase the structural stability of the material and reduce structural collapse during the charge and discharge cycle, thereby improving the cycle life. Titanium can improve the electrochemical stability and structural integrity of the material, and help enhance the rate performance. Nickel can increase conductivity and improve the overall conductivity and capacity of the material. Aluminum can enhance the thermal stability and corrosion resistance of the material.
[0009] Optionally, the doping element is introduced via its salt, the salt of magnesium is magnesium nitrate, the salt of titanium is titanium dioxide, the salt of nickel is nickel nitrate, and the salt of aluminum is aluminum nitrate.
[0010] Optionally, the conductive polymer is pyrrole, and the coating thickness of the conductive polymer is 5 to 10 nm.
[0011] A method for preparing a sodium ion battery positive electrode material with high cycle performance comprises the following steps:
[0012] S1: Na source and Mn source were mixed in molar ratio and dissolved in deionized water, then ethanol and citric acid were added, and stirred at 80-90°C for 1-3h to form a uniform and transparent sol;
[0013] S2: Weigh magnesium nitrate, titanium dioxide, nickel nitrate, and aluminum nitrate, dissolve them in deionized water to prepare their respective precursor solutions, then gradually add the doping precursor solutions to the main sol, and stir for 30 to 60 minutes to obtain a mixed sol;
[0014] S3: heating the mixed sol to 85-95° C. and continuously stirring until the solution thickens to form a gel, and then placing the gel in a drying oven and drying it at 120-150° C. for 10-15 hours to remove moisture and organic solvent to obtain a dry doping precursor powder;
[0015] S4: The dried precursor powder is evenly distributed in a ceramic crucible, placed in a tube furnace, and argon protective gas is introduced. The temperature is raised to 700-800°C at a rate of 5°C / min and maintained for 1-2h, then raised to 850-950°C at a rate of 3°C / min and maintained for 8-12h, and finally cooled to room temperature to obtain doped Na x Mn y O2 cathode material;
[0016] S5: The doped positive electrode material powder is dispersed in a 0.05-0.15M concentration of pyrrole monomer solution, and after ultrasonic stirring for 20-40 minutes, a 0.03-0.07M concentration of ammonium persulfate solution is slowly added, and the mixture is stirred at room temperature for 3-5 hours for polymerization coating, followed by washing with deionized water and drying at 80-100°C for 4-8 hours, and finally heat-treating at 250-300°C for 1-3 hours to complete the formation of the conductive polymer coating layer.
[0017] Optionally, the Na source in step S1 is sodium carbonate, and the Mn source is manganese dioxide.
[0018] Optionally, in step S1, the volume of water is 8 to 12 times the total mass of the solute, the volume of ethanol is 20 to 40% of the total solution, and the mass of citric acid is 3 to 7% of the total solute mass.
[0019] Optionally, in step S5, 10 mL of pyrrole monomer solution and 20 mL of ammonium persulfate solution are required for every 1 gram of positive electrode material powder.
[0020] Optionally, the pyrrole monomer solution is obtained by dissolving pyrrole raw material in deionized water, and the ammonium persulfate solution is obtained by dissolving ammonium persulfate as an oxidant in deionized water.
[0021] After adopting the above technical solution, the present invention has the following beneficial effects compared with the prior art. Of course, any product implementing the present invention does not necessarily need to achieve all the advantages described below at the same time:
[0022] The sodium ion battery positive electrode material of the present invention can optimize the electrochemical performance of the material by doping magnesium, titanium, nickel and aluminum in a layered transition metal oxide matrix, wherein the doping of magnesium and titanium improves the structural stability and thermal stability of the material, the introduction of nickel enhances the conductivity, and the doping of aluminum reduces the volume change of the material, effectively improving the rate performance and cycle stability of the material; at the same time, the corrosion and side reactions of the electrolyte are further reduced by the conductive polymer surface coating, which significantly prolongs the service life and cycle performance of the battery, and can maintain a good capacity retention rate under high rate charge and discharge conditions.
[0023] The specific implementation modes of the present invention are further described in detail below in conjunction with the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] The drawings described below are only some embodiments. For those skilled in the art, other drawings can be obtained based on these drawings without creative work. In the drawings:
[0025] Figure 1 for Na x Mn y SEM images of O2 cathode materials, where (a) is the Na prepared in Example 1 x Mn y O2 positive electrode material, (b) Na prepared in Example 2 x Mn y O2 positive electrode material, (c) Na prepared in Example 3 x Mn y O2 positive electrode material.
[0026] It should be noted that these drawings and textual descriptions are not intended to limit the conceptual scope of the present invention in any way, but are intended to illustrate the concept of the present invention for those skilled in the art by referring to specific embodiments. DETAILED DESCRIPTION
[0027] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0028] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0029] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0030] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present application description and examples are exemplary only.
[0031] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0032] See also Figure 1 As shown, in this embodiment, a sodium ion battery positive electrode material with high cycle performance is provided, and the positive electrode material is a layered transition metal oxide Na x Mn y O2 is doped with magnesium, titanium, nickel and aluminum elements, and the doping ratio is 5-10% for magnesium, 2-5% for titanium, 8-12% for nickel and 3-7% for aluminum, and the surface is coated with a conductive polymer, wherein 0.5≤x≤1.0 and 0.5≤y≤1.0.
[0033] In some embodiments of the present invention, the doping element is introduced through its salt, the salt of magnesium is magnesium nitrate, the salt of titanium is titanium dioxide, the salt of nickel is nickel nitrate, and the salt of aluminum is aluminum nitrate.
[0034] In some embodiments of the present invention, the conductive polymer is pyrrole, and the coating thickness of the conductive polymer is 5-10 nm.
[0035] A sodium ion battery positive electrode material with high cycle performance and a preparation method thereof, comprising the following steps:
[0036] S1: Na source and Mn source were mixed in molar ratio and dissolved in deionized water, then ethanol and citric acid were added, and stirred at 80-90°C for 1-3h to form a uniform and transparent sol;
[0037] S2: Weigh magnesium nitrate, titanium dioxide, nickel nitrate, and aluminum nitrate, dissolve them in deionized water to prepare their respective precursor solutions, then gradually add the doping precursor solutions to the main sol, and stir for 30 to 60 minutes to obtain a mixed sol;
[0038] S3: heating the mixed sol to 85-95° C. and continuously stirring until the solution thickens to form a gel, and then placing the gel in a drying oven and drying it at 120-150° C. for 10-15 hours to remove moisture and organic solvent to obtain a dry doping precursor powder;
[0039] S4: The dried precursor powder is evenly distributed in a ceramic crucible, placed in a tube furnace, and argon protective gas is introduced. The temperature is raised to 700-800°C at a rate of 5°C / min and maintained for 1-2h, then raised to 850-950°C at a rate of 3°C / min and maintained for 8-12h, and finally cooled to room temperature to obtain doped Na x Mn y O2 positive electrode material.
[0040] S5: The doped positive electrode material powder is dispersed in a 0.05-0.15M concentration of pyrrole monomer solution, and after ultrasonic stirring for 20-40 minutes, a 0.03-0.07M concentration of ammonium persulfate solution is slowly added, and the mixture is stirred at room temperature for 3-5 hours for polymerization coating, followed by washing with deionized water and drying at 80-100°C for 4-8 hours, and finally heat-treating at 250-300°C for 1-3 hours to complete the formation of the conductive polymer coating layer.
[0041] In some embodiments of the present invention, the Na source in step S1 is sodium carbonate, and the Mn source is manganese dioxide.
[0042] In some embodiments of the present invention, in step S1, the volume of water is 8 to 12 times the total mass of the solute, the volume of ethanol is 20 to 40% of the total solution, and the mass of citric acid is 3 to 7% of the total solute mass.
[0043] In some embodiments of the present invention, in step S5, 10 mL of pyrrole monomer solution and 20 mL of ammonium persulfate solution are required for every 1 gram of positive electrode material powder.
[0044] In some embodiments of the present invention, the pyrrole monomer solution is prepared by dissolving the pyrrole raw material in deionized water, and the ammonium persulfate solution is prepared by dissolving ammonium persulfate as an oxidant in deionized water.
[0045] The present invention will now be further described in detail with reference to embodiments.
[0046] It should be noted that all raw materials in the examples of the present invention were obtained through commercial sources.
[0047] In the following examples, the Na source and Mn source are Na2CO3 and MnO2, respectively.
[0048] Embodiment 1: A method for preparing a positive electrode material for a sodium ion battery with high cycle performance, comprising the following steps:
[0049] S1: Dissolve Na2CO3 and MnO2 in 10 times the volume of deionized water at a molar ratio of 0.8:1.0, add 30% volume of ethanol and 5% mass of citric acid, and stir at 85°C for 2h to form a uniform and transparent sol.
[0050] S2: Weigh magnesium nitrate, titanium dioxide, nickel nitrate and aluminum nitrate, dissolve them in deionized water to form a precursor solution, gradually add them to the main sol and stir for 45 minutes to obtain a uniform mixed sol.
[0051] S3: The mixed sol was heated to 90°C and stirred until it thickened to form a gel, and then dried at 120°C for 12 h to obtain a dry doping precursor powder.
[0052] S4: The precursor powder was heated to 750°C at 5°C / min under argon protection and maintained for 1 h, then heated to 900°C at 3°C / min and maintained for 10 h, and cooled to room temperature to obtain Na-doped x Mn y O2 positive electrode material.
[0053] S5: The cathode material powder was dispersed in 0.1 M pyrrole monomer solution and ultrasonically stirred for 30 min. After adding 0.05 M ammonium persulfate solution, it was stirred at room temperature for 4 h. After washing and drying, it was heat treated at 260 °C for 2 h.
[0054] Embodiment 2: A method for preparing a positive electrode material for a sodium ion battery with high cycle performance, comprising the following steps:
[0055] S1: Dissolve Na2CO3 and MnO2 in 12 times the volume of deionized water at a molar ratio of 0.9:1.0, add 25% volume of ethanol and 4% mass of citric acid, and stir at 80°C for 1.5h to form a uniform and transparent sol.
[0056] S2: The same doping elements as in Example 1 were dissolved in deionized water and gradually added to the main sol and stirred for 40 min to obtain a uniform mixed sol.
[0057] S3: Heat the mixed sol to 88° C., continue stirring until a gel is formed, and dry at 130° C. for 10 h to obtain a dry doping precursor powder.
[0058] S4: The precursor powder was heated to 760°C at 4°C / min under argon protection and maintained for 1.5 h, then heated to 900°C at 2°C / min and maintained for 11 h, and cooled to room temperature to obtain doped Na x Mn y O2 positive electrode material.
[0059] S5: The positive electrode material powder was dispersed in 0.08M pyrrole monomer solution and ultrasonically stirred for 25 minutes. After adding 0.04M ammonium persulfate solution, it was stirred at room temperature for 3.5 hours. After washing and drying, it was heat treated at 270°C for 1.5 hours.
[0060] Embodiment 3: A method for preparing a positive electrode material for a sodium ion battery with high cycle performance, comprising the following steps:
[0061] S1: Dissolve Na2CO3 and MnO2 in 11 times the volume of deionized water at a molar ratio of 0.7:1.0, add 35% volume of ethanol and 6% mass of citric acid, and stir at 88°C for 2.5h to form a uniform and transparent sol.
[0062] S2: The same doping element as in Example 1 was used, dissolved in deionized water and gradually added to the main sol and stirred for 50 min to obtain a uniform mixed sol.
[0063] S3: The mixed sol was heated to 92° C. and stirred to form a gel, and dried at 140° C. for 14 h to obtain a dry doping precursor powder.
[0064] S4: The precursor powder was heated to 800°C at 5°C / min under argon protection and maintained for 1 h, then heated to 950°C at 3°C / min and maintained for 12 h, and cooled to room temperature to obtain doped Na x Mn y O2 positive electrode material.
[0065] S5: The positive electrode material powder was dispersed in 0.12M pyrrole monomer solution and ultrasonically stirred for 35min. After adding 0.06M ammonium persulfate solution, it was stirred at room temperature for 4.5h. After washing and drying, it was heat treated at 280℃ for 2h.
[0066] Experimental example: positive electrode material testing
[0067] The prepared doped positive electrode material was mixed with the conductive agent and polyvinylidene fluoride in a mass ratio of 8:1:1. The mixture was dispersed in N-methyl-2-pyrrolidone solvent and stirred into a uniform slurry. The slurry was coated on the aluminum foil current collector, spread evenly and dried in a vacuum drying oven at 120°C for 12 hours to form a positive electrode sheet. The dried positive electrode sheet was pressed into the required thickness and cut into electrode sheets of appropriate size. The battery was assembled in a glove box using the prepared positive electrode sheet, metal sodium negative electrode sheet, separator and electrolyte. Then, the battery and battery tester were used for the experiment. First, a constant current charge and discharge test was performed at a rate of 0.1C on the battery tester. The first discharge capacity of the battery was recorded as the initial discharge capacity. Then, a cyclic charge and discharge test was performed at a rate of 0.1C, and the discharge capacity of each cycle was recorded. After 200 charge and discharge cycles, the retention rate of the discharge capacity was calculated. Then, a constant current charge and discharge test was performed at a rate of 0.5C. The test at each rate includes first fully charging at a rate of 0.1C and then discharging at a rate of 0.5C. Finally, the discharge capacity at each rate is recorded, and the capacity change of the material at different discharge rates is analyzed to evaluate its rate performance. The experimental data of Examples 1-3 and the control example are shown in Table 1.
[0068] Table 1: Comparison table of Examples 1-3 and Control Examples
[0069]
[0070] As can be seen from Table 1, the material of Example 1 shows lower charge transfer impedance and ion diffusion impedance due to the reasonable combination of doping elements and uniform polymer coating. This enables the material to maintain a higher capacity at high rates, and will not cause significant capacity decay due to increased internal resistance. Specifically, the initial discharge capacity of Example 1 is 182mAh / g, which is significantly higher than Example 2 (178mAh / g) and Example 3 (175mAh / g). This shows that the material of Example 1 can store more sodium ions during the first charge and discharge process, reflecting a higher specific capacity. After 200 charge and discharge cycles, the capacity retention rate of Example 1 is 92%, which is higher than 90% of Example 2 and 88% of Example 3. This means that the material of Example 1 maintains better electrochemical stability during long cycles, indicating that the material structure is more stable and the loss caused by the insertion and removal of sodium ions is less. The discharge capacity of Example 1 at a rate of 0.5C is 170mAh / g, which is also better than Example 2 (165mAh / g) and Example 3 (160mAh / g). This indicates that at a higher discharge rate, the material of Example 1 can still maintain a higher capacity, reflecting its superior rate performance and good rapid charge and discharge capability.
[0071] Furthermore, from Figure 1It can be seen from (a) that the SEM image of Example 1 shows a highly uniform and dense layered structure, with a very smooth surface, clear edges and no obvious cracks or holes, and the material has a tightly packed layered structure, indicating that the material particles are in good contact and arrangement, and there are no obvious structural defects. The uniform and dense layered structure helps to improve the specific capacity of the electrode material, because a tighter arrangement can provide more active sites while reducing the penetration of the electrolyte and the occurrence of side reactions. In addition, the smooth surface and tight structure make the material less prone to structural collapse or pulverization during the charge and discharge cycle, thereby improving the cycle life. Finally, the tight structure can provide a continuous electron conduction path, reduce the internal resistance of the electrode, and improve the conductivity and rate performance.
[0072] from Figure 1 (b) shows that the SEM image of Example 2 shows a slightly uneven layered structure with some rough areas on the surface, small cracks and slight defects. The layered structure of the material is more obvious, but compared with Example 1, the interlayer arrangement is slightly loose, and small gaps and cracks appear in some areas.
[0073] from Figure 1 (c) shows that the SEM image of Example 3 shows an irregular and porous structure with obvious cracks, uneven surface and a large number of holes. The layered structure of the material is not obvious, the distribution between particles is uneven, and there are obvious pores and cracks, indicating that the structure of the material is loose and uneven.
[0074] In summary, it can be seen from the SEM images that the Na x Mn y The O2 cathode material has the best morphology and structure, which is manifested in a uniform and dense layered structure, a smooth surface and clear edges, which optimizes the electrochemical performance and cycle stability. In contrast, the morphology and structure of Examples 2 and 3 gradually deteriorate, showing more cracks and pores, which will reduce the overall performance of the battery, especially in the case of high rate and long cycle use.
[0075] The present invention is not limited to the above-mentioned embodiments. Anyone should be aware that any structural changes made under the enlightenment of the present invention, and any technical solutions that are the same or similar to the present invention, fall within the protection scope of the present invention. The technology, shape, and structural parts not described in detail in the present invention are all well-known technologies.
Claims
1. A sodium ion battery positive electrode material with high cycle performance, characterized in that: The positive electrode material is layered transition metal oxide Na x Mn y O2 is doped with magnesium, titanium, nickel and aluminum elements, and the doping ratio is 5-10% for magnesium, 2-5% for titanium, 8-12% for nickel and 3-7% for aluminum, and the surface is coated with a conductive polymer, wherein 0.5≤x≤1.0 and 0.5≤y≤1.
0.
2. A sodium ion battery positive electrode material with high cycle performance according to claim 1, characterized in that: The doping elements are introduced through their salts. The salt of magnesium is magnesium nitrate, the salt of titanium is titanium dioxide, the salt of nickel is nickel nitrate, and the salt of aluminum is aluminum nitrate.
3. A sodium ion battery positive electrode material with high cycle performance according to claim 1, characterized in that: The conductive polymer is pyrrole, and the coating thickness of the conductive polymer is 5 to 10 nm.
4. A method for preparing a sodium ion battery positive electrode material with high cycle performance, characterized in that: The following steps are involved: S1: Na source and Mn source were mixed in molar ratio and dissolved in deionized water, then ethanol and citric acid were added, and stirred at 80-90°C for 1-3h to form a uniform and transparent sol; S2: Weigh magnesium nitrate, titanium dioxide, nickel nitrate, and aluminum nitrate, dissolve them in deionized water to prepare their respective precursor solutions, then gradually add the doping precursor solutions to the main sol, and stir for 30 to 60 minutes to obtain a mixed sol; S3: heating the mixed sol to 85-95° C. and continuously stirring until the solution thickens to form a gel, and then placing the gel in a drying oven and drying it at 120-150° C. for 10-15 hours to remove moisture and organic solvent to obtain a dry doping precursor powder; S4: The dried precursor powder is evenly distributed in a ceramic crucible, placed in a tube furnace, and argon protective gas is introduced. The temperature is raised to 700-800°C at a rate of 5°C / min and maintained for 1-2h, then raised to 850-950°C at a rate of 3°C / min and maintained for 8-12h, and finally cooled to room temperature to obtain doped Na x Mn y O2 cathode material; S5: The doped positive electrode material powder is dispersed in a 0.05-0.15M concentration of pyrrole monomer solution, and after ultrasonic stirring for 20-40 minutes, a 0.03-0.07M concentration of ammonium persulfate solution is slowly added, and the mixture is stirred at room temperature for 3-5 hours for polymerization coating, followed by washing with deionized water and drying at 80-100°C for 4-8 hours, and finally heat-treating at 250-300°C for 1-3 hours to complete the formation of the conductive polymer coating layer.
5. The method for preparing a sodium ion battery positive electrode material with high cycle performance according to claim 4, characterized in that: In step S1, the Na source is sodium carbonate, and the Mn source is manganese dioxide.
6. The method for preparing a sodium ion battery positive electrode material with high cycle performance according to claim 4, characterized in that: In step S1, the volume of water is 8 to 12 times the total mass of the solute, the volume of ethanol is 20 to 40% of the total solution, and the mass of citric acid is 3 to 7% of the total mass of the solute.
7. The method for preparing a sodium ion battery positive electrode material with high cycle performance according to claim 4, characterized in that: In step S5, 10 mL of pyrrole monomer solution and 20 mL of ammonium persulfate solution are required for every 1 gram of positive electrode material powder.
8. The method for preparing a sodium ion battery positive electrode material with high cycle performance according to claim 4, characterized in that: The pyrrole monomer solution is obtained by dissolving the pyrrole raw material in deionized water, and the ammonium persulfate solution is obtained by dissolving ammonium persulfate as an oxidant in deionized water.
Citation Information
Cited By
Nickel salt modified sulfurized anthryl polymer as well as preparation method and application thereof
CN120484260A